2021
DOI: 10.1108/aeat-03-2021-0092
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tab corner geometry on supersonic jets

Abstract: Purpose The purpose of this study is to evaluate the effect of tabs having different corner geometries on the flow characteristics of a supersonic convergent–divergent (C-D) nozzle. Design/methodology/approach A circular C-D nozzle of Mach 2.0 was used, and the tabs were positioned at the exit of the nozzle in diametrically opposite directions. Three tabs having different corner geometry implemented in the experiments were rectangular tab with triangular top edge, triangular tab with a bell-shaped edge and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…All the above mentioned authors examined the profile modification, whereas Arun Kumar et al (2019) found that the correct position to place the tab against the nozzle exit is first shock crossover point. Subsequently, a paper by Quadros et al (2021) investigated the effect of shape modification on rectangular tabs. Investigators Rao et al (2020) experimentally studied the mixing rates of lobbed nozzle and elliptical nozzle.…”
Section: Introductionmentioning
confidence: 99%
“…All the above mentioned authors examined the profile modification, whereas Arun Kumar et al (2019) found that the correct position to place the tab against the nozzle exit is first shock crossover point. Subsequently, a paper by Quadros et al (2021) investigated the effect of shape modification on rectangular tabs. Investigators Rao et al (2020) experimentally studied the mixing rates of lobbed nozzle and elliptical nozzle.…”
Section: Introductionmentioning
confidence: 99%